Migration and Public Expenditure: the Host Country Point of view - Giorgio Basevi; Alessandro Tarozzi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1997)
The flows of migration from neighbouring countries into the European Union have, since its inception, been more relevant than those of internal migration. Thus, labour movements from relatively less industrialized countries of the EU —such as Italy in the 50's—towards the relatively more advanced ones —such as France and Germany—quickly vanished after the European Community was established among the initial six members. Later, migration from Portugal and Spain towards the richer EU countries was again greatly reduced, when those countries, as Italy and Greece before them, also became members of the Community. Migration flows from Turkey, on the other hand, were slowed down only by specific restrictions, particularly in Germany, and will probably be no longer relevant once the customs union between the EU and Turkey is completed. In the meantime, migrants from Southern Mediterranean, Eastern European, and other extra-EU countries keep pressing at the EU borders. The recent flow of illegal immigrants from Albania, particularly into Italy and Greece, is only the latest and more dramatised example of a larger and continuing phenomenon.
Keywords: 330